The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc04334f
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimetallic {LnOVPt} complexes with antiferromagnetic Ln–V coupling and magnetic memory

Abstract: PtVO(SOCR)4 lantern complexes and Ce(OAr)3 or Nd(OAr)3 form heterotrimetallic [Ln(OAr)3{PtVO(SOCR)4}] with linear Ln–OVPt linkages; all four exhibit slow magnetic relaxation and likely antiferromagnetic coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Compared to organic molecular wires, molecules containing transition metal centers have the potential for enhanced conductance , and increased functionality via redox or magnetic properties which can be leveraged to create components such as molecular switches and memory storage devices. , Metal-centered electronic states or nuclear spin states of molecules containing one or more transition metals can be synthetically tuned and manipulated in situ for potential applications in spintronics and quantum information science (QIS). Synthetic efforts to form molecular metal wires include coordination polymers, extended metal atom chains (EMACs), and infinite one-dimensional (1D) chains. …”
Section: Introductionmentioning
confidence: 99%
“…Compared to organic molecular wires, molecules containing transition metal centers have the potential for enhanced conductance , and increased functionality via redox or magnetic properties which can be leveraged to create components such as molecular switches and memory storage devices. , Metal-centered electronic states or nuclear spin states of molecules containing one or more transition metals can be synthetically tuned and manipulated in situ for potential applications in spintronics and quantum information science (QIS). Synthetic efforts to form molecular metal wires include coordination polymers, extended metal atom chains (EMACs), and infinite one-dimensional (1D) chains. …”
Section: Introductionmentioning
confidence: 99%
“…Heterometallic complexes have been studied in many research fields such as luminescence, [1][2][3] catalysis, [4][5][6] and magnetism. [7][8][9][10][11][12][13][14] Luminescence has received particular interest because of its utilization in luminescence devices, bioimaging systems, and photosensitizers. Hasegawa et al…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have thus been devoted to the formation of various intermetallic interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although highresolution X-ray diffraction analysis can provide insight into the electron density of bonds, 19 theoretical calculations are widely conducted for examining intermetallic interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this study, we synthesized heterometallic Ln-Pt complexes:…”
Section: Introductionmentioning
confidence: 99%
“…Heterometallic complexes have been studied in many research fields such as luminescence, catalysis, and magnetism. Luminescence has received particular interest because of its utilization in luminescence devices, bioimaging systems, and photosensitizers. Hasegawa et al reported the thermocontrol emission of a heterometallic Tb­(III)–Eu­(III) polymer, wherein the energy transfer from the Tb to Eu ion is governed by the thermosensitivity dependence on linker ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heterometallic interactions also exert an important influence on the physical properties of heterometallic complexes. Considerable efforts have thus been devoted to the formation of various intermetallic interactions. Although high-resolution X-ray diffraction analysis can provide insight into the electron density of bonds, theoretical calculations are widely conducted for examining intermetallic interactions. …”
Section: Introductionmentioning
confidence: 99%